Evaluasi User Experience pada Aplikasi BCA Mobile dan MyBCA dengan menggunakan Metode Usability Testing dan User Experience Questionnaire (UEQ) - Hansen Natanael; Aryo Pinandito; Mochamad Chandra Saputra (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2023)
BCA Mobile and MyBCA are two mobile banking apps offered by BCA. Users of BCA Mobile have complained about issues with signal indicator lights, a large number of steps required and a lack of a